New parties, new policies? The influence of radical right parties on immigration policies - Valentin Tim Zacharias Berger (Frontiers in Political Science, 2025)
Radical right parties are widely regarded as influential political actors, particularly in the domain of immigration policy. In recent times, greater attention has been directed towards the potential influence of these new parties on the output of the legislative process. As radical right parties are predominantly opposition parties, the radical right aims to exert indirect effects. The article extends research on the indirect policy effects of the radical right on immigration legislation. By utilizing the concepts of salience and distance in policy preferences, the article provides a more accurate depiction of the radical right’s potential for policy influence than previous accounts. The analysis encompasses 11 West European democracies from 1985 to 2017, a period that covers the consolidation of radical right parties. The results of linear regressions with country fixed effects illustrate that indirect effects by the radical right are not a pivotal element of immigration policy change. In the event of conservative office holders, radical right parties, however, have the capacity to exert an indirect effect on policy reforms through the interplay of salience and distance in policy preferences. An indirect effect is also evident in the highly symbolic sub-area securitization of immigration. The article provides evidence that new parties can influence the political future of a country through their indirect influence in shaping immigration policy. Whilst the influence on political competitors has been frequently discussed, the article demonstrates that the consequences of the radical right extend to public policy.